2015
DOI: 10.2967/jnumed.115.158881
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Imaging of Post-Src Inhibition Tumor Signatures for Guiding Dasatinib Combination Therapy

Abstract: Noninvasive, real-time, quantitative measurement of key biomarkers associated with cancer therapeutic interventions could provide a better understanding of cancer biology. We investigated in this study whether incorporating multiple molecular imaging approaches could be used to guide dasatinib anti-Src therapy and aid in the rational design of a combination therapy regimen. Methods: Bioluminescence imaging, 18 F-FDG PET, integrin α v β 3 -targeted SPECT/ CT, and vascular endothelial growth factor-targeted near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…In a new study, Gao et al reported that the Src inhibitor dasatinib reduced the uptake of 99m Tc-3PRGD2 in a dasatinib-resistant A549 human non-small cell lung cancer model 45 . They attributed this effect to the down-regulation of the host (murine) integrin β3 and the reduced RGD binding affinity for tumor (human) integrin α v β 3 because the expression of the tumor (human) integrin α v β 3 did not change according to the IHC assays.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a new study, Gao et al reported that the Src inhibitor dasatinib reduced the uptake of 99m Tc-3PRGD2 in a dasatinib-resistant A549 human non-small cell lung cancer model 45 . They attributed this effect to the down-regulation of the host (murine) integrin β3 and the reduced RGD binding affinity for tumor (human) integrin α v β 3 because the expression of the tumor (human) integrin α v β 3 did not change according to the IHC assays.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, additional studies are necessary to investigate the interrelations between the uptake of RGD-based tracers and the integrins from host-guest origins following anti-cancer drug treatments, such as AAT. Furthermore, another question was raised for those two reports 18 , 45 whether RGD peptides alone could be sufficient enough to reflect tumor response to dasatinib therapy since dasatinib treatment lead to the uptake reduction of the radiolabeled RGD in both dasatinib-responsive U87MG tumor and dasatinib-resistant A549-fLuc tumor model. To strengthen the current study, a sunitinib-resistant tumor model is really necessary.…”
Section: Discussionmentioning
confidence: 99%
“…The 4T1 murine breast cancer cell line was obtained from the American Type Culture Collection. Firefly luciferase stably transfected 4T1 (4T1-fLuc) cells were generated using a previously described method 22 . Cells were maintained in RPMI 1640 medium (Invitrogen, Carlsbad, CA) supplemented with 10% fetal bovine serum (FBS) at 37°C in humidified atmosphere containing 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Other researchers have had similar findings, with Zhang and colleagues, in 2011 [34], using early time point imaging of AngioSense 750 to show that anti-VEGF treatment normalizes vascularity and decreases vascular leak. In a well-designed MIBA-2 study, Gao, et al [35] established that A549-luc tumor size, bioluminescence, and [ 18 F]FDG uptake were unaffected after 7 days of dasatinib treatment (Fig. 3, left panel).…”
Section: Miba Strategies In Cancermentioning
confidence: 99%